Sing, unburied, sing [large type] : a novel - Ward, Jesmyn (Wheeler Publishing, a part of Gale, a Cengage Company, 2017)
Ward (Salvage the Bones) tells the story of three generations of a struggling Mississippi family in this astonishing novel. "We don't walk no straight lines. It's all happening at once. All of it. We all here at once." This is the explanation 13-year-old Jojo is provided by his grandmother, the family matriarch, on her deathbed. "I'll be on the other side of the door," she reassures him, "With everybody else that's gone before." Jojo and his little sister, Kayla, live with their grandparents, while Leonie, their mother, drifts in and out of their lives, causing chaos. Snorting coke one night, Leonie explains, "A clean burning shot through my bones, and then I forgot. The shoes I didn't buy, the melted cake ..." Leonie wants to be a better mother, and when Jojo's and Kayla's father is released from prison, Leonie takes the kids with her, hoping for a loving reunion, but what she gets instead is a harrowing drive across a muggy landscape haunted by hatred. Throughout the novel, though, are beautifully crafted moments of tenderness. When the dead, including Leonie's murdered brother, make their appearances and their demands, no one in the family's surprised. But their stories are deeply affecting, in no small part because of Ward's brilliant writing and compassionate eye. (Sept.) © Copyright PWxyz, LLC. All rights reserved.